Analysis of Students’ Science Process Skills in Physics Material in Online Learning - Rufaida, Salwa; Riskawati, Riskawati; Sindi, Sindi (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to analyze the science process skills possessed by students during online learning on physics material. The type of research used is descriptive research with a quantitative approach. In this study, instruments of physics science process skills will be distributed to 30 students of class XI who are in the top 10 at three high schools in Gowa Regency that are still implementing the online learning system to date, namely SMA Aksara Bajeng, SMA Handayani Sungguminasa, and SMAN 19 Gowa. Science process skills instruments are shared online. The data obtained were analyzed using descriptive analysis. The results showed that in general the science process skills possessed by the dominant students were in the low category with the highest frequency of 13 people, 12 people in the medium category, 4 people in the very low category and 1 person in the high category. Meanwhile, for each indicator of science process skills, of the 7 indicators, there are 4 indicators that are in the low category and 3 indicators are in the medium category. So it can be concluded that the students’ science process skills on physics material in dominant online learning are still relatively low.